Investigation and Experimentation on Ancient Egyptian Tattooing Methods - Pászik, Jenny (Zeitschrift für ägyptische Sprache und Altertumskunde, 2021)
The aim of this research is to use experimental archaeology and comparative studies in order to obtain a potential answer to the theory that UC 7790 is a set of tattooing implements. Comparing the tools, methods, and inks of other cultures that practice tattooing is a way to offer some guidance regarding the identification of tattooing tools in the archaeological record. The experiment reproduced the original points using the closest modern metal and tested each one with an organic mixture of charcoal and water, and Indian ink as a control ink. The reproduced needles are tested on pigskin and human skin to test efficacy and healing. The experiment proves that UC 7790 may have been tattoo needles as they successfully tattoo human skin and were probably hafted implements.